Implementing a novel PAM-4 modulation/demodulation scheme along with source and link protection in a high capacity data center architecture - Baozhu Li; Salman Ghafoor; Jawad Mirza; Bilal Aziz; Muhammad Ijaz; Ahmad Almogren (PLoS ONE, 2026)
Desirable data-center features include cost efficiency, high bandwidth, scalability, and protection against component failures. In this study, we propose an architecture that employs a small number of optical sources to transport data over a large number of links inside a data center. To further increase the bandwidth, two bits per symbol are transmitted by employing a novel technique for the generation and demodulation of pulse amplitude modulated (PAM) signals having a data rate of 100 Gbps. The proposed architecture provides protection against two major sources of breakdown, the laser source and the channel used for the transmission of signals. Furthermore, diversity gain can also be achieved by simultaneously transmitting the same optical signals through different channels inside the data center. The performance of the proposed architecture is observed in terms of bit error rate under different amplified spontaneous emission (ASE) noise powers.